SSR MARKER BASED PARENT SELECTION OF MAIZE ( ARENT SELECTION OF MAIZE (Zea mays Zea mays L.) INBRED LINES L.) INBRED LINES - RAJESH KUMAR, SHASHI KUMAR; NILMANI PRAKASH, AJAY KUMAR; SANTOSH KUMAR, PANKAJ KUMAR; VINAY KUMAR, GAUTTAM KUMAR (The Bioscan, 2018)
An experiment was designed to study the molecular diversity present in eighteen maize inbred lines during Kharif – 2016-17. A panel of thirteen highly polymorphic SSR primers generated allelic variants ranging from seven in the cases of nc133, umc1161, umc1367 and umc1196 to ten in the cases of, phi029, umc1332, phi034 and umc1266. A total of 110 alleles were detected among the eighteen maize inbred lines with an average of 8.46 alleles per locus. The PIC value was found to vary from 0.805 in the case of umc1367 to 0.886 in the case of phi065 with an average of 0.849 per primer. Analysis of divergence pattern based on SSR markers allowed differentiation of maize inbred lines into basically three clusters. The large range of similarity coefficient revealed by SSR markers provided greater confidence for the assessment of genetic divergence and interrelationship among the maize inbred lines. A perusal of similarity coefficients clearly reflected that a very high degree of similarity exists between maize genotypes Pool 33- 193 and Pool 34- 193, whereas CML-165 and HKI-586 found more diverse, may be used in breeding programme to generate more recombinants. Use of SSR markers appeared more efficient in achieving unique and unambiguous characterization and differentiation of maize inbred lines used in the present study. The SSR analysis also revealed unique or variety specific allele, which could be useful as DNA fingerprints in the identification and preservation of maize genotypes.